China –Pakistan Educational and Cultural Cooperation Under BRI - Kamran, Taj; Dr. Hussan Ara Magsi (Pacific International Journal, 2023)
China-Pakistan Economic Corridor (CPEC) is a mega-investment project that has accelerated Pakistan’s socio-economic growth. Pakistan’s higher education sector is one key area to be upgraded under CPEC. Since the conclusion of CPEC agreement in 2015, Sino-Pakistan collaboration in higher education is expanding. Beijing is offering scholarships, vocational training and Chinese language courses to Pakistani youth and providing opportunities for academic and research collaboration. This study is an attempt to examine China’s effective employment of higher education as a soft power tool to increase its influence and prestige in Pakistan. It argues that growing educational cooperation is fostering intercultural linkages as well as faculty and students’ mobility between Pakistan and China. The article suggests that Islamabad needs to expand cooperation with Beijing in areas such as faculty development, emerging fields of science and technology, industry-university linkages and digital collaboration of technology in higher education sector.